Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{4}{9}+\dfrac{5}{8}\)=\(\dfrac{32}{72}+\dfrac{45}{72}=\dfrac{77}{72}\)
\(\dfrac{6}{10}+\dfrac{9}{2}=\dfrac{6}{10}+\dfrac{45}{10}=\dfrac{51}{10}\)
\(\dfrac{10}{2}-\dfrac{5}{2}=\dfrac{5}{2}\)
\(\dfrac{8}{8}x1=\dfrac{8}{8}x\dfrac{1}{1}=\dfrac{8}{8}\)
\(\dfrac{8}{9}:\dfrac{3}{7}=\dfrac{56}{27}\\ \dfrac{8}{9}+\dfrac{2}{5}=\dfrac{58}{45}\\ \dfrac{7}{8}-\dfrac{1}{3}=\dfrac{13}{24}\\ \dfrac{3}{10}\times\dfrac{1}{6}=\dfrac{1}{20}\\ 1\dfrac{2}{7}+6\dfrac{5}{6}=\dfrac{9}{7}+\dfrac{41}{6}=\dfrac{341}{42}\\ 5\dfrac{3}{4}-\dfrac{1}{5}=\dfrac{23}{4}-\dfrac{1}{5}=\dfrac{111}{20}\\ 6\dfrac{2}{9}:4\dfrac{7}{10}=\dfrac{56}{9}:\dfrac{47}{10}=\dfrac{560}{423}\\ \dfrac{5}{3}+\dfrac{3}{2}-\dfrac{7}{6}=2\)
\(a.\frac{7}{5}+\frac{4}{7}-\frac{9}{10}=\frac{98}{70}+\frac{40}{70}-\frac{63}{70}=\frac{98+40-63}{70}=\frac{75}{70}\)\(=\frac{15}{14}\)
\(b.2+\frac{3}{4}x\frac{8}{5}=2+\frac{6}{5}=\frac{16}{5}\)
\(c.\frac{9}{8}-\frac{6}{5}:\frac{8}{5}=\frac{9}{8}-\frac{6}{5}x\frac{5}{8}=\frac{9}{8}-\frac{6}{8}=\frac{3}{8}\)
\(\dfrac{7}{5}+\dfrac{4}{7}-\dfrac{9}{10}=\dfrac{49-20}{35}-\dfrac{9}{10}=\dfrac{19}{35}-\dfrac{9}{10}=\dfrac{190-315}{350}=\dfrac{-125}{350}\)
\(\dfrac{2}{1}+\dfrac{3}{4}\text{×}\dfrac{8}{5}=\dfrac{8+3}{4}\text{×}\dfrac{8}{5}=\dfrac{11\text{×}8}{4\text{×}5}=\dfrac{88}{20}\)
mấy câu kia áp dụng là dc!
a) \(\dfrac{5}{7}\times\dfrac{5}{9}+\dfrac{4}{9}\times\dfrac{5}{7}\)
\(=\dfrac{5}{7}\times\left(\dfrac{4}{9}+\dfrac{5}{9}\right)\)
\(=\dfrac{5}{7}\times1\)
\(=\dfrac{5}{7}\)
b) \(\dfrac{1}{10}+\dfrac{5}{9}+\dfrac{4}{9}+\dfrac{9}{10}-1\)
\(=\left(\dfrac{5}{9}+\dfrac{4}{9}\right)+\left(\dfrac{1}{10}+\dfrac{9}{10}-1\right)\)
\(=1+0\)
\(=1\)
c) \(\dfrac{5}{7}\times\dfrac{5}{9}+\dfrac{4}{9}\times\dfrac{5}{7}+\dfrac{2}{7}\)
\(=\dfrac{5}{7}\times\left(\dfrac{5}{9}+\dfrac{4}{9}\right)+\dfrac{2}{7}\)
\(=\dfrac{5}{7}+\dfrac{2}{7}\)
\(=1\)
d) \(\dfrac{2}{7}+\dfrac{2}{8}+\dfrac{1}{4}+\dfrac{1}{7}+\dfrac{4}{7}\)
\(=\left(\dfrac{2}{8}+\dfrac{1}{4}\right)+\left(\dfrac{2}{7}+\dfrac{1}{7}+\dfrac{4}{7}\right)\)
\(=\left(\dfrac{1}{4}+\dfrac{1}{4}\right)+1\)
\(=\dfrac{1}{2}+1\)
\(=\dfrac{3}{2}\)
e) \(\dfrac{4}{5}+\dfrac{3}{10}+\dfrac{2}{10}+0,7\)
\(=\dfrac{4}{5}+\dfrac{5}{10}+\dfrac{7}{10}\)
\(=\dfrac{4}{5}+\dfrac{12}{10}\)
\(=\dfrac{4}{5}+\dfrac{6}{5}\)
\(=\dfrac{10}{5}\)
\(=2\)
g) \(362\times728+326\times272\)
\(=326\times\left(728+272\right)\)
\(=326\times1000\)
\(=326000\)
\(\frac{8}{10}xr=\frac{5}{9}\)
\(r=\frac{5}{9}:\frac{8}{10}\)
\(r=\frac{25}{36}\)
\(\frac{8}{10}\)\(xr\)\(=\frac{5}{9}\)
\(r=\frac{5}{9}\)\(:\frac{8}{10}\)\(=\frac{5}{9}\)\(x\frac{10}{8}\)\(=\frac{25}{36}\)